Polysilicon breakage filling packaging bag and polysilicon packaging body
Patent Information
- Application Number
- CN202280016000.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-08
- Filing Date
- 2022-03-01
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-03-01
AI Technical Summary
在这样的状态下,由于内袋并不具备气体阻隔性,因此在单晶提拉之前多晶硅破碎物就会被污染,这也是一个问题
[0019]根据本发明的多晶硅破碎物填充用包装袋,由于其最内层具有不含添加剂的聚乙烯系树脂层,因此能够防止被填充的多晶硅破碎物与包装袋接触而导致的污染。进一步地,由于其具有气体阻隔层,因此能够有效地防止刚将多晶硅破碎物填充于包装袋之后直到马上要使用之前因与外部空气接触而使污染性气体透过从而导致上述多晶硅破碎物被污染。
Smart Images

Figure CN116963970B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a novel packaging bag for filling polysilicon fragments used in semiconductor manufacturing materials, etc. More specifically, the invention provides a packaging bag for filling polysilicon fragments that more effectively prevents the polysilicon fragments from being contaminated by outside air immediately after packaging. Background Technology
[0002] High-purity rod-shaped polycrystalline silicon is mainly manufactured using the Siemens process and used as a raw material for manufacturing monocrystalline silicon, which is used as a raw material for semiconductor devices, etc. The Siemens process is a method of growing high-purity rod-shaped polycrystalline silicon by vapor-phase growth through heating a high-purity silicon seed crystal (core wire) with an electric current, causing a reaction between silane-based gas and hydrogen on the surface of the seed crystal.
[0003] Polycrystalline silicon manufactured using the Siemens process is formed into rods, which are sometimes broken and packaged or packed as fragments of polycrystalline silicon and transported to monocrystalline and polycrystalline silicon manufacturing plants, etc.
[0004] If necessary, the aforementioned polycrystalline silicon fragments are etched to remove surface impurities, and then filled into packaging bags made of polyethylene resin film to prevent contamination. Generally, they are transported in shipping boxes such as corrugated cardboard boxes.
[0005] However, in recent years, regarding pollution from polysilicon fragments, the following phenomenon has been pointed out: after polysilicon fragments are filled into the aforementioned packaging bags and packaged, polluting gases can permeate through the polyethylene resin film and contaminate the polysilicon fragments. Countermeasures have been proposed to address this issue. Examples of polluting gases include water vapor in the outside air, volatile organic compounds (such as diethyl phthalate (DEP), dibutyl phthalate (DBP), and other organic components from the environment), and metal vapors.
[0006] For example, the following countermeasures were taken: polycrystalline silicon fragments were packaged in a double-layered bag consisting of an inner bag and an outer bag made of polyethylene resin, and a structure was made that imparts gas barrier properties to the outer bag, thereby preventing the polycrystalline silicon fragments from being contaminated (see Patent Document 1).
[0007] Thus, previous anti-contamination measures all provided gas barrier properties to the outer bag. On the other hand, the current situation regarding the packaging bag that forms the inner bag, which comes into direct contact with the polycrystalline silicon fragments, is that, in order to prevent contamination of the polycrystalline silicon fragments, it is made of only a layer of polyethylene resin film without additives.
[0008] However, the inventors have confirmed that contamination caused by polluting gases permeating through the packaging bag begins immediately after the filling of the polysilicon fragments. Even with conventional measures that provide gas barriers to the outer bag, contamination due to polluting gases can still occur during the period between filling the polysilicon into the packaging bag and placing it into the outer bag. Therefore, it is clear that even if the outer bag is provided with gas barriers, this type of contamination cannot be completely prevented.
[0009] Furthermore, when performing single-crystal pulling using polycrystalline silicon fragments, the polycrystalline silicon fragments are typically introduced into the cleanroom with the outer bag removed. In this state, because the inner bag lacks gas barrier properties, the polycrystalline silicon fragments can become contaminated before single-crystal pulling, which is also a problem.
[0010] Existing technical documents
[0011] Patent documents
[0012] Patent Document 1: Japanese Patent Application Publication No. 2010-195425 Summary of the Invention
[0013] The problem that the invention aims to solve
[0014] Therefore, the object of the present invention is to provide a packaging bag for filling polycrystalline silicon fragments, which can more effectively prevent external air from contaminating the polycrystalline silicon fragments from the time the packaging is completed until the polycrystalline silicon fragments are used.
[0015] means for solving problems
[0016] To solve the aforementioned problems, the inventors conducted repeated and dedicated research. According to conventional wisdom, to prevent contamination of polycrystalline silicon fragments, packaging bags for directly packaging polycrystalline silicon fragments are typically made of a single layer of additive-free polyethylene resin film. However, the inventors overturned this conventional wisdom and discovered that packaging bags can be constructed from a laminated body with a specific layer structure, including the aforementioned additive-free polyethylene resin layer as the innermost layer. Furthermore, they found that using this packaging bag effectively prevents contamination caused by the permeation of polluting gases from contact with outside air immediately after the polycrystalline silicon fragments are filled into the packaging bag until the immediate time of use, thus ultimately completing this invention.
[0017] That is, the packaging bag for filling polycrystalline silicon fragments according to one aspect of the present invention is a packaging bag for directly packaging polycrystalline silicon fragments. The packaging bag is characterized in that it is composed of multiple layers of film, wherein the innermost layer is disposed of as a polyethylene resin layer without additives, and at least a gas barrier layer and a reinforcing material layer are laminated on the polyethylene resin layer.
[0018] The effects of the invention
[0019] The packaging bag for filling polycrystalline silicon fragments according to the present invention, having an innermost layer of additive-free polyethylene resin, prevents contamination caused by contact between the filled polycrystalline silicon fragments and the packaging bag. Furthermore, having a gas barrier layer, it effectively prevents contamination of the polycrystalline silicon fragments by allowing polluting gases to permeate through contact with outside air immediately after filling the packaging bag and before use. Attached Figure Description
[0020] Figure 1 This is a schematic cross-sectional view showing a representative shape of the packaging bag for filling polycrystalline silicon fragments according to the present invention. Detailed Implementation
[0021] Figure 1 The diagram shows a cross-sectional view of a representative form of the polycrystalline silicon fragment filling packaging bag 1 of the present invention. See also... Figure 1 The packaging bag 1 for filling polycrystalline silicon fragments is used for directly packaging polycrystalline silicon fragments. The packaging bag 1 is characterized by being composed of multiple layers of film, wherein the innermost layer is a polyethylene resin layer 2 without additives, and at least a gas barrier layer 3 and a reinforcing material layer 4 are laminated on the polyethylene resin layer 2. The polycrystalline silicon fragments are obtained by mechanically crushing rod-shaped polycrystalline silicon manufactured using the Siemens process or similar methods.
[0022] The polyethylene resin in the additive-free polyethylene resin layer 2 of the packaging bag 1 for filling polycrystalline silicon fragments of the present invention is an additive-free polyethylene resin that does not contain additives that would contaminate the polycrystalline silicon fragments. There are no particular limitations on the type of additive-free polyethylene resin; known resins that have been used for packaging polycrystalline silicon fragments since the past can be used. Examples of such polyethylene resins include low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), and LLDPE using a metallocene catalyst (hereinafter also referred to as metallocene LLDPE). Among these, LLDPE and metallocene LLDPE, which exhibit excellent puncture resistance when forming the layer, are preferred.
[0023] To prevent contamination caused by contact between the inner surface of the packaging and the broken polycrystalline silicon material being filled, the aforementioned additive-free polyethylene resin layer 2 needs to be placed in the innermost layer.
[0024] Ideally, the metal contamination on the surface of the additive-free polyethylene resin layer 2 should be as low as possible. The preferred surface metal concentration obtained by extraction and analysis using hydrofluoric acid is 15 pg / cm³ for Fe. 2 The following values show that Cr is 5 pg / cm³. 2 The following values are for Ni, which is 5 pg / cm³. 2 The following values are for Cu: 5 pg / cm³ 2 The following values for Zn are 10 pg / cm³. 2 The following is an Al value of 50 pg / cm³. 2 The following is an example of a Ca concentration of 20 pg / cm³. 2 the following.
[0025] The thickness of the additive-free polyethylene resin layer 2 is not particularly limited, but considering wear caused by contact with broken polycrystalline silicon, it is preferably 20 μm or more, and particularly preferably 30 μm or more. Furthermore, regarding its upper limit, considering the reduction in flexibility due to its overlap with other layers, it is preferably 200 μm or less, and particularly preferably 100 μm or less.
[0026] The gas barrier layer 3 constituting the polycrystalline silicon crushed material filling packaging bag 1 of the present invention is disposed on the outer layer of the additive-free polyethylene resin layer 2. The gas barrier layer 3 inhibits the permeation of polluting gases through the polycrystalline silicon crushed material filling packaging bag 1 into the bag, thereby preventing the polycrystalline silicon crushed material from being contaminated immediately after packaging. In addition, the gas barrier layer 3 also has the effect of inhibiting the permeation of water vapor through the polycrystalline silicon crushed material filling packaging bag 1 into the bag. Generally, the lower the water vapor permeability, the lower the organic matter permeability; therefore, the lower the water vapor permeability, the better the effect of preventing the polycrystalline silicon crushed material from being contaminated.
[0027] There are no particular limitations on the material of the gas barrier layer 3, and any known material with excellent function in preventing the permeation of the aforementioned polluting gases can be used. Examples include inorganic materials such as silicon dioxide and aluminum, and resins such as polyvinyl alcohol. Generally, the gas barrier layer is formed by using the aforementioned inorganic material as a vapor-deposited film and the resin as a laminated film.
[0028] In terms of the material of the gas barrier layer 3, silicon oxide is particularly preferred as an inorganic material to prevent the packaged polycrystalline silicon fragments from being contaminated by metal. That is, the gas barrier layer 3 is particularly preferably a vapor-deposited film of silicon oxide.
[0029] The optimal thickness of the gas barrier layer 3 can be appropriately determined considering the aforementioned material. Specifically, it can be determined as follows: in the multilayer film constituting the packaging bag 1 for filling polycrystalline silicon fragments, the water vapor permeability is 1.2 g / m. 2 For doses below 1 day, 0.7 g / m² is preferred. 2 For temperatures below 1 day, 0.5 g / m² is preferred. 2 • Less than 1000 nm. In order to achieve this performance, in the case of the above-mentioned inorganic vapor-deposited film, it is preferable to make it with a thickness of 30 nm or more, and more preferably 50 nm or more, while in the case of resin, it is preferable to make it with a thickness of 0.01 μm or more, and more preferably 0.1 μm or more.
[0030] Furthermore, if the gas barrier layer 3 is very thick, the flexibility of the polycrystalline silicon fragment filling packaging bag 1 will be reduced. Therefore, in the case of the above-mentioned inorganic vapor-deposited film, its thickness is preferably 150 nm or less, while in the case of resin, its thickness is preferably 50 μm or less.
[0031] The reinforcing material layer 4 constituting the polycrystalline silicon fragment filling packaging bag 1 of the present invention is provided on the outer layer of the additive-free polyethylene resin layer 2. The reinforcing material layer 4 is used to prevent the polycrystalline silicon fragment filling packaging bag 1 from being stretched due to the filling of polycrystalline silicon fragments, thereby preventing damage to the gas barrier layer. The reinforcing material layer 4 can impart stable anti-pollution performance to the polycrystalline silicon fragment filling packaging bag 1.
[0032] The material and structure of the reinforcing layer 4 can be anything that prevents the multilayer film constituting the polysilicon crushed material packaging bag 1 from experiencing tensile stress during the filling of polysilicon crushed materials. Specifically, there are no particular limitations on the multilayer film constituting the polysilicon crushed material packaging bag 1, and any known reinforcing film capable of imparting a puncture strength of 10N or more, preferably 12N or more, as measured according to JIS-Z1707, can be used. If the puncture strength of the multilayer film is within the above range, it can prevent the sharp corners of the polysilicon crushed material inside the packaging bag 1 from puncturing the packaging bag during transportation, thus preventing the polysilicon from coming into contact with the outside air and causing contamination.
[0033] Furthermore, while thickening the aforementioned additive-free polyethylene resin layer 2 can also achieve the function of reinforcing the material, it may compromise the flexibility of the packaging bag.
[0034] To provide a specific example of the reinforcing material layer 4, examples include films made of polyethylene terephthalate (PET), nylon, or other polyamide resins with an aliphatic backbone, perforated films, or nonwoven fabrics made of the aforementioned materials. From the viewpoint of improving the puncture strength of the multilayer film constituting the packaging bag 1 for filling polycrystalline silicon fragments, the reinforcing material layer 4 preferably contains a polyamide resin with an aliphatic backbone, and more preferably contains PET and a polyamide resin with an aliphatic backbone.
[0035] Examples of polyamide resins with an aliphatic backbone include polymers of condensation units such as nylon 6, nylon 11, nylon 12, nylon 46, nylon 66, nylon 69, nylon 610, and nylon 612, or copolymers of two or more of these. Among these, nylon 6 and nylon 66 are preferred.
[0036] Regarding the amount of polyamide resin with an aliphatic backbone contained in the reinforcing material layer 4, from the viewpoint of improving the puncture strength of the multilayer film constituting the packaging bag 1 for filling polycrystalline silicon fragments, it is preferably 50% by mass or more, more preferably 60% by mass or more, relative to 100% by mass of the material constituting the reinforcing material layer 4. Furthermore, from the viewpoint of reducing flexibility, it is preferably 90% by mass or less, more preferably 80% by mass or less.
[0037] In the polycrystalline silicon crushed material filling packaging bag 1 of the present invention, when a substrate layer is required in the formation of the gas barrier layer, such as when a gas barrier layer is formed by vapor deposition, the above-mentioned reinforcing material layer 4 can also be used as the above-mentioned substrate layer.
[0038] Furthermore, regarding the lower limit of the thickness of the aforementioned reinforcing material layer 4, from the viewpoint of puncture strength, it is preferably 10 μm or more, and more preferably 20 μm or more. Regarding the upper limit of the thickness of the aforementioned reinforcing material layer 4, from the viewpoint of reducing flexibility, it is preferably 50 μm or less, and more preferably 40 μm or less.
[0039] In the polycrystalline silicon crushed material filling packaging bag 1 of the present invention, the total thickness of the multilayer film is 300 μm or less, and preferably 200 μm or less in terms of the processability of the packaging bag and the ease of welding of the opening.
[0040] In the packaging bag 1 for filling polycrystalline silicon fragments of the present invention, regarding the multilayer film, as long as the innermost layer is composed of a polyethylene resin layer 2, the stacking order of the other layers is not particularly limited. For example, it can be as follows: Figure 1As shown, the gas barrier layer 3 and the reinforcing material layer 4 are stacked in this order on the polyethylene resin layer 2. Alternatively, the reinforcing material layer 4 and the gas barrier layer 3 can be stacked in this order on the polyethylene resin layer 2. The configuration where the gas barrier layer 3 is the intermediate layer and the reinforcing material layer (i.e., the reinforcing material layer 4 is placed on the outermost layer) is preferred because it effectively prevents damage to the gas barrier layer.
[0041] In particular, the arrangement of layering a reinforcing material layer, a gas barrier layer, and another reinforcing material layer in this order on the innermost polyethylene resin layer is preferred because it further improves the strength of the packaging bag and enhances the protection against damage to the gas barrier layer.
[0042] Alternatively, other functional material layers that do not affect the present invention may be laminated. Furthermore, regarding the bonding method of each layer when forming the above-mentioned multilayer film, it can be appropriately determined as welding, bonding, etc., depending on the material of each layer.
[0043] In this invention, there are no particular limitations on the form of the packaging bag 1 for filling the polycrystalline silicon fragments; a known form may be used. For example, such as... Figure 1 The flat bag or square-bottom bag shown is a typical shape.
[0044] The polycrystalline silicon package formed by filling the polycrystalline silicon crushed material into the aforementioned polycrystalline silicon crushed material filling bag 1 is also included within the scope of this invention.
[0045] In this invention, there are no particular restrictions on the polycrystalline silicon fragments filled in the above-mentioned polycrystalline silicon fragment filling packaging bag 1, and they can have known dimensions, but it is preferred for polycrystalline silicon fragments with an average major diameter (average maximum wafer length) of 5 to 150 mm, especially 30 to 110 mm.
[0046] In addition, regarding the size of the aforementioned packaging bag 1 for filling polycrystalline silicon fragments, the weight of the polycrystalline silicon being filled is generally 5 kg or 10 kg.
[0047] The polysilicon crushing material filling packaging bag 1 of the present invention can be shipped directly after filling with polysilicon crushing material, or it can be used as an inner bag and sealed inside an outer bag. That is, a double-layer polysilicon packaging body formed by sealing the aforementioned polysilicon packaging body inside an outer bag is also included within the scope of the present invention. Known materials and shapes can be appropriately used as the outer bag. Typically, a flat bag or a square-bottom bag made of polyethylene resin film is preferred as the outer bag.
[0048] [Overview]
[0049] A packaging bag for filling polycrystalline silicon fragments according to one aspect of the present invention is characterized in that the packaging bag for filling polycrystalline silicon fragments is a packaging bag for directly packaging polycrystalline silicon fragments, the packaging bag for filling polycrystalline silicon fragments is composed of multiple layers of film, wherein the innermost layer is provided with a polyethylene resin layer without additives, and at least a gas barrier layer and a reinforcing material layer are stacked on the polyethylene resin layer.
[0050] According to the above-mentioned packaging bag for filling polycrystalline silicon fragments, the gas barrier layer can be a vapor-deposited film of silicon oxide.
[0051] According to the above-mentioned packaging bag for filling polycrystalline silicon fragments, the reinforcing material layer may be a resin layer containing a polyamide resin having an aliphatic backbone.
[0052] According to the above-mentioned packaging bag for filling polycrystalline silicon fragments, the above-mentioned reinforcing material layer can be disposed on the outermost layer of the above-mentioned multilayer film.
[0053] According to the above-mentioned packaging bag for filling polycrystalline silicon fragments, the puncture strength of the above-mentioned multilayer film, as measured according to JIS-Z1707, can be above 10N.
[0054] One aspect of the present invention relates to a polycrystalline silicon package, which is a polycrystalline silicon package made by filling polycrystalline silicon fragments into the aforementioned polycrystalline silicon fragment filling packaging bag.
[0055] According to one aspect of the invention, the polycrystalline silicon package contains polycrystalline silicon fragments, wherein the average maximum length of the filled fragments is 5 to 150 mm.
[0056] One aspect of the present invention relates to a double-layer polycrystalline silicon packaging body, which is formed by sealing the aforementioned polycrystalline silicon packaging body into an outer bag made of a polyethylene resin film.
[0057] Example
[0058] The following embodiments are shown to illustrate the invention in more detail, but the invention is not limited to these embodiments.
[0059] Furthermore, in the embodiments, various measurements were performed using the following methods.
[0060] (1) Method for measuring impurity concentration on the surface of polycrystalline silicon fragments
[0061] 40g of polycrystalline silicon fragments were transferred to a clean 500ml PTFE beaker, and 100ml of a dissolving solution (10ml of 50% HF and 90ml of 70% nitric acid) was added. Extraction was performed at 25°C for 15 minutes. The liquid components in the PTFE beaker and the surface of the polycrystalline silicon fragments were washed with 100ml of ultrapure water. The washing solution was transferred to a clean PTFE beaker and used as the surface extract of the polycrystalline silicon fragments. The surface extract of the polycrystalline silicon fragments was evaporated to dry and solidify. A 3.5% nitric acid aqueous solution was added, and the volume was adjusted to 20.0ml. ICP-MS was performed to determine the metal concentrations on each surface and calculate the concentration values relative to the total weight of the polycrystalline silicon fragments.
[0062] [Example 1]
[0063] As a multilayer film, a polyethylene terephthalate film (total thickness 12μm, consisting of a 30μm thick, additive-free polyethylene resin layer 2, a 0.05μm thick silicon oxide vapor-deposited film as a gas barrier layer 3, and a 20μm thick polyethylene terephthalate reinforcing layer 4) is used, stacked in this order. The resulting packaging bag for filling polycrystalline silicon fragments is a flat bag measuring 30cm × 60cm, with the additive-free polyethylene resin layer 2 heat-sealed as the innermost layer. Furthermore, the puncture strength of the multilayer film constituting the above-mentioned polycrystalline silicon fragment filling packaging bag is 25N, and the water vapor transmission rate is 0.4g / m². 2 • Day. Additionally, the metal concentration on the inner surface of the packaging bag used to fill the aforementioned polycrystalline silicon fragments, obtained by extraction and analysis using hydrofluoric acid, is as follows: Fe = 5 pg / cm³. 2 Cr is 1 pg / cm 2 Ni is 1 pg / cm 2 Cu is 1 pg / cm 2 Zn is 5 pg / cm³ 2 Al is 25 pg / cm 2 Ca is 10 pg / cm 2 .
[0064] On the other hand, in a cleanroom maintained at a cleanliness level of 4, etched polycrystalline silicon fragments with an average major diameter of 45 mm were filled into a polycrystalline silicon fragment filling bag at a rate of 5 kg using a funnel. After filling, the opening was immediately sealed by heat sealing to obtain a polycrystalline silicon package. Fifty of these polycrystalline silicon packages were manufactured, placed in the cleanroom for 5 hours, and then placed outside the cleanroom for 12 hours. They were then transported back to the cleanroom, and each package was immediately opened. Five polycrystalline silicon fragments were randomly selected from each package, and the surface impurity concentration was measured. The average concentrations of impurity elements were as follows: Fe 10 pptw, Cr 1 pptw, Ni 1 pptw, Cu 1 pptw, Zn 5 pptw, Al 5 pptw, and Ca 10 pptw. Furthermore, organic components from the environment were measured by gas chromatography, and no peaks for DEP or DBP were detected.
[0065] Furthermore, in the examples and comparative examples, the quantification of organic components from the environment was calculated using 100 ng of standard samples of DEP, DBP, and dioctyl phthalate (DOP) based on the peak area ratio.
[0066] [Comparative Example 1]
[0067] Without a gas barrier layer, and correspondingly, the thickness of the polyethylene resin layer (excluding additives) in the multilayer film is set to 50 μm. Otherwise, polycrystalline silicon fragments are filled in the same manner as in Example 1, and a polycrystalline silicon package is manufactured. The puncture strength of the multilayer film constituting the above-mentioned polycrystalline silicon fragment filling packaging bag is 14 N, and the water vapor transmission rate is 1.3 g / m². 2 ·sky.
[0068] The obtained polycrystalline silicon packages were placed in a cleanroom for 5 hours and then outside for 12 hours. Afterward, they were moved to the cleanroom, and each package was immediately opened. Five random polycrystalline silicon fragments were taken from each package, and the surface impurity concentration was measured. The average concentrations of the impurity elements were as follows: Fe 20 pptw, Cr 5 pptw, Ni 5 pptw, Cu 1 pptw, Zn 10 pptw, Al 10 pptw, and Ca 50 pptw. Additionally, organic components from the environment were measured using the same method as in the examples. Peaks for DEP and DBP were detected, and the quantitative results were as follows: DEP 60 pptw and DBP 100 pptw.
[0069] [Example 2]
[0070] The reinforcing layer 4 was changed to a 20 μm thick reinforcing layer composed of polyethylene terephthalate (PET) and nylon 6. Otherwise, polycrystalline silicon fragments were filled in the same manner as in Example 1, and a polycrystalline silicon package was manufactured. The mass ratio of PET to nylon in the reinforcing layer 4 (PET:Nylon) was 1:1.5. The puncture strength of the multilayer film constituting the polycrystalline silicon fragment filling packaging bag was 30 N, and the water vapor transmission rate was 0.4 g / m³. 2 ·sky.
[0071] The obtained polycrystalline silicon packages were placed in a cleanroom for 5 hours and then outside for 12 hours. Afterward, they were moved to the cleanroom, and each package was immediately opened. Five random polycrystalline silicon fragments were taken from each package, and the surface impurity concentration was measured. The average concentrations of impurity elements were as follows: Fe 12 pptw, Cr 2 pptw, Ni 1 pptw, Cu 0 pptw, Zn 4 pptw, Al 5 pptw, and Ca 15 pptw. Furthermore, organic components from the environment were measured by gas chromatography, and no peaks for DEP or DBP were detected.
[0072] [Example 3]
[0073] After filling polycrystalline silicon fragments in the same manner as in Example 1, an outer bag made of polyethylene is formed, thereby creating a double-layer polycrystalline silicon packaging body. The puncture strength of the multilayer film constituting the above-mentioned polycrystalline silicon fragment filling packaging bag is 20N, and the water vapor transmission rate is 0.4g / m. 2 ·sky.
[0074] Regarding the obtained double-layer polycrystalline silicon packaging, it was placed in a cleanroom for 5 hours and then outside the cleanroom for 12 hours. Afterward, the outer bag was opened, and only the polycrystalline silicon packaging was moved into the cleanroom. Each packaging was immediately opened, and five random polycrystalline silicon fragments were taken from each packaging to measure the surface impurity concentration. The average concentrations of the impurity elements were as follows: Fe 20 pptw, Cr 5 pptw, Ni 5 pptw, Cu 1 pptw, Zn 10 pptw, Al 10 pptw, and Ca 50 pptw. Additionally, organic components from the environment were measured using the same method as in the examples. Peaks for DEP and DBP were detected, and the quantitative results were as follows: DEP 60 pptw and DBP 100 pptw.
[0075] Furthermore, in the examples and comparative examples, the quantification of organic components from the environment was calculated using 100 ng of standard samples of DEP, DBP, and DOP based on the peak area ratio.
[0076] [Comparative Example 2]
[0077] Without a gas barrier layer, and correspondingly, the thickness of the polyethylene resin layer (excluding additives) in the multilayer film is set to 50 μm. Otherwise, polycrystalline silicon fragments are filled in the same manner as in Example 1, and then a bag with a gas barrier layer (similar to that in Example 1) is used as the outer bag to manufacture a double-layer polycrystalline silicon packaging. The puncture strength of the multilayer film constituting the above-mentioned polycrystalline silicon fragment filling packaging bag is 20 N, and the water vapor transmission rate is 0.4 g / m². 2 ·sky.
[0078] Regarding the obtained double-layer polycrystalline silicon packaging, it was placed in a cleanroom for 5 hours and then outside the cleanroom for 12 hours. Afterward, the outer bag was opened, and only the polycrystalline silicon packaging was moved into the cleanroom. Each packaging was immediately opened, and five random polycrystalline silicon fragments were taken from each packaging to measure the surface impurity concentration. The average concentrations of the impurity elements were as follows: Fe 20 pptw, Cr 5 pptw, Ni 5 pptw, Cu 1 pptw, Zn 10 pptw, Al 10 pptw, and Ca 50 pptw. Additionally, organic components from the environment were measured using the same method as in the examples. Peaks for DEP and DBP were detected, and the quantitative results were as follows: DEP 50 pptw, DBP 50 pptw.
[0079] No caprolactam was detected on the surface of the polycrystalline silicon packages in Examples 1, 2, 3, and Comparative Example 1. The caprolactam content was measured by gas chromatography.
[0080] The evaluation results for the polysilicon packages of Examples 1, 2 and Comparative Example 1 are shown in Table 1.
[0081] Table 1
[0082]
[0083] Symbol Explanation
[0084] 1. Packaging bags for filling polycrystalline silicon fragments
[0085] 2. Polyethylene resin layer
[0086] 3. Gas barrier layer
[0087] 4. Strengthen the material layer
Claims
1. A packaging bag for filling broken polycrystalline silicon materials, characterized in that, The packaging bag for filling polycrystalline silicon fragments is a packaging bag used for directly packaging polycrystalline silicon fragments. The packaging bag for filling polycrystalline silicon fragments is composed of multiple layers of film. In the multiple layers of film, the innermost layer is a polyethylene resin layer without additives, and at least a gas barrier layer and a reinforcing material layer are stacked on the polyethylene resin layer. in The metal concentration extracted and analyzed from the surface of the additive-free polyethylene resin layer using hydrofluoric acid was 15 pg / cm³ for Fe. 2 Below; Cr is 5 pg / cm 2 Below; Ni is 5 pg / cm 2 Below; Cu is 5 pg / cm 2 The following values indicate that Zn is 10 pg / cm³. 2 Below; Al is 50 pg / cm 2 Below; Ca is 20 pg / cm 2 The following; and When the packaging bag filled with polycrystalline silicon fragments was placed outside the cleanroom for 12 hours, and then moved into the cleanroom and the polycrystalline silicon fragments were removed, no DEP or DBP was detected on the polycrystalline silicon fragments taken out of the packaging bag.
2. The packaging bag for filling polycrystalline silicon fragments according to claim 1, wherein, The gas barrier layer is a vapor-deposited film of silicon oxide.
3. The packaging bag for filling polycrystalline silicon fragments according to claim 1, wherein, The reinforcing material layer is a resin layer containing a polyamide resin with an aliphatic backbone.
4. The packaging bag for filling polycrystalline silicon fragments according to claim 1, wherein, The reinforcing material layer is disposed on the outermost layer of the multilayer film.
5. The packaging bag for filling polycrystalline silicon fragments according to claim 1, wherein, The puncture strength of the multilayer film, as measured according to JIS-Z1707, is above 25 N.
6. A polycrystalline silicon package, which is a polycrystalline silicon package made by filling polycrystalline silicon fragments into a polycrystalline silicon fragment filling bag according to any one of claims 1 to 5.
7. The polycrystalline silicon package according to claim 6, wherein, The average maximum length of the filled polycrystalline silicon fragments is 5 to 150 mm.
8. A double-layer polycrystalline silicon packaging body, which is formed by sealing the polycrystalline silicon packaging body of claim 6 or 7 into an outer bag made of polyethylene resin film.
Citation Information
Patent Citations
Packing body and packing method for silicon
JP2010195425A
Packaging bag
JP2020015207A
Sealant, bag for transportation of silicon material, and package of silicon material
WO2021039922A1